Więzienie jako kara kryminalna. Kilka uwag o współczesnych problemach izolacji penitencjarnej - Tomasz Kalisz (Wrocławsko-Lwowskie Zeszyty Prawnicze)
The penalty of imprisonment must be applied very carefully and taking into account all the costs and negative consequences of isolation and assuming limited possibilities to achieve social rehabilitation goals. This does not imply that this form of criminal law reaction to prohibited acts should be abandoned. The need to reform the penalty of deprivation of liberty and to seek effective organizational forms for penitentiary systems should be confirmed by the size of the population of criminally incarcerated people around the world, and especially the trends in this area. Criticism of punishments based on isolation often boils down to low effectiveness, high economic and social costs and a number of negative consequences in the individual sphere, directly related to very deep interference in the sphere of human rights and freedoms. In practice, we are dealing with a clear paradox consisting in the creation of a repressive institution in its real character and a social rehabilitation institution in the space of expectations.